2018
DOI: 10.5530/jyp.2018.10.69
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Prescribers towards Electronic Prescription: A Pre-Implementation Evaluation

Abstract: Objective: Electronic (e) prescribing is computerised prescribing. The Government of Kerala has started the e-health initiative. The objective of this study was to obtain the perceptions of prescribing doctors on e-prescription before its implementation. Method: This was a questionnaire based cross sectional study conducted for a period of six months in a Government tertiary care teaching hospital of Kerala. The prescribing doctors of the institution formed the sample population. The response to the structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 14 publications
2
22
1
Order By: Relevance
“…A survey conducted in India in 2018 proved that only 45% of local doctors agreed that electronic prescribing was faster and easier than traditional prescribing. In addition, 35.8% of the Indian respondents stated that e-prescribing interrupted their workflow [ 31 ]. E-prescribing may only be fully accepted by doctors if they are strongly convinced that the technology has a positive impact on their effectiveness and efficiency [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey conducted in India in 2018 proved that only 45% of local doctors agreed that electronic prescribing was faster and easier than traditional prescribing. In addition, 35.8% of the Indian respondents stated that e-prescribing interrupted their workflow [ 31 ]. E-prescribing may only be fully accepted by doctors if they are strongly convinced that the technology has a positive impact on their effectiveness and efficiency [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Indian survey indicated that around 60% of Indian doctors had experienced technical problems and needed regular support [ 31 ]. In turn, a Chinese study confirmed the hypothesis that the greater organisational support that exists at the healthcare centre level, the use of e-prescribing will be more widespread [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the systems currently used in healthcare centers is the electronic prescribing system. The electronic prescribing system uses computerized communication networks to store and transfer physician orders to the pharmacy at the point of care (1;2). Previous studies (29) have shown that using the electronic prescribing system enhances the efficiency of care providers, improves patient safety, reduces medical costs, increases the effectiveness of services provided, enables access to the patient's medication history and the monitoring of medication interactions, improves medical outcomes, and reduces healthcare expenses.…”
Section: Introductionmentioning
confidence: 99%
“…One of the systems currently used in medical centers is the electronic prescribing system. The electronic prescribing system uses computerized communication networks to store and transfer physician orders to the pharmacy at the point of care [1,2]. Previous studies [2][3][4][5][6][7][8][9] have shown that using the electronic prescribing system enhances the efficiency of care providers, improves patient safety, reduces medical costs, increases the effectiveness of services provided, enables access to the patient's medication history and the monitoring of medication interactions, improves medical outcomes and reduces health care expenses.…”
Section: Introductionmentioning
confidence: 99%